Factors affecting the intention to hire people with Down syndrome : Hierarchical Multiple Linear Regression Analysis - Md Mizanur, Rahman; Ting, Chuong Hock; Razitasham, Safii; Rosalia, Saimon; Chen, Yoke Yong; Sharifa Ezat, Wan Puteh; Abg. Safuan, Adenan (MALQUE Publishing, 2024)
Introduction: The employability of people with Down syndrome remains a critical issue because misconceptions and discrimination often overshadow their abilities and potential in the workforce. This study used hierarchical multiple linear regression and moderation analysis to investigate factors influencing the intention to hire people with Down syndrome.